2015
DOI: 10.3855/jidc.5815
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan fasting and infectious diseases: a systematic review

Abstract: Ramadan represents the fourth of the five pillars of the Islamic creed. Although patients are exempted from observing this duty, they may be eager to share this moment of the year with their peers. However, there are no guidelines that can help physicians to address the concerns of patients with infectious diseases fasting during Ramadan. For this purpose, we performed a systematic review. of 51 articles. Our main findings are that: 1) patients suffering from diabetes at risk of developing infectious complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…[141516] The main purpose of fasting the holy month is to attain righteousness. [17] Some other benefits include strengthening the believers' relationship with their Creator (His name is Allah), having self-reflection and appreciation of Allah's blessings, remembering and helping the people in need, and learning self-control.…”
Section: Benefits Of Fasting the Holy Monthmentioning
confidence: 99%
See 3 more Smart Citations
“…[141516] The main purpose of fasting the holy month is to attain righteousness. [17] Some other benefits include strengthening the believers' relationship with their Creator (His name is Allah), having self-reflection and appreciation of Allah's blessings, remembering and helping the people in need, and learning self-control.…”
Section: Benefits Of Fasting the Holy Monthmentioning
confidence: 99%
“…[1521222324] However, many exempt Muslim patients with chronic medical conditions (e.g., diabetes) may still choose to fast. They may discontinue their medications or alter treatment regimens to fast with/out consulting their primary care physicians (PCPs).…”
Section: Exemptions From Fasting Ramadanmentioning
confidence: 99%
See 2 more Smart Citations
“…[34] Moreover, in patients with diabetes, it is demonstrated that Ramadan Fasting can lead to an increased risk of infection. [35] Notwithstanding all aforementioned evidence in favor or against the practice of Ramadan Fasting in terms of infection risk, there is no conclusive evidence to acknowledge or refute increased susceptibility of fasting individuals to contracting Covid-19 infection. Similarly, no evidence has emerged indicating that drinking water during daytime can prevent corona virus infection in healthy individuals.…”
mentioning
confidence: 99%